Stylistic approach to biblical based writing. - Quek, Elaine Yi Xian. (2011)
The Bible is often used in works of literature to explore various issues and situations present in society. This is what I seek to do in my creative piece, The Blessings of Zack. I reworked the story of Jacob and Esau from the Bible by placing it in a contemporary setting based in Singapore. By doing so, I hoped to further explore the themes of betrayal and identity as suggested in the Bible from the story of Jacob and Esau. Through The Blessings of Zack, I wish to introduce some possible ways to deal with the issues of betrayal and the search for identity in today’s context. My aim in this essay is to discuss the stylistic approach I took to writing my creative piece, and the decisions I made with regards to staying with or straying from the story written in the Bible. The main questions I want to address are: how close do authors stay to Biblical stories, where do they deviate, and how do they handle it? To tackle these questions, I will make a close comparison of Gopal Baratham’s Kissful of Tears and Philip Jeyaretnam’s Abraham’s Promise with my writing. Some points of comparison in our stylistic approach are the parallelism to events in the Bible, narrative perspective, the naming of characters, and the themes discussed. By the end of this comparison, I hope to have shown the reasons for choosing the stylistic decisions I made, and have argued how my approach in contrast to the two writers allowed me to better deal with the themes of betrayal and identity.